2021
DOI: 10.3390/toxins13080508
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-PT Antibody Response after Pertussis Vaccination and Infection: The Importance of Both Quantity and Quality

Abstract: Pertussis toxin (PT) is considered the main virulence factor causing whooping cough or pertussis. The protein is widely studied and its composition was revealed and sequenced already during the 1980s. The human immune system creates a good response against PT when measured in quantity. However, the serum anti-PT antibodies wane rapidly, and only a small amount of these antibodies are found a few years after vaccination/infection. Therefore, multiple approaches to study the functionality (quality) of these anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 123 publications
1
7
0
Order By: Relevance
“…Repeated antigenic stimulation leads to the selection of B cells that bear a receptor able to bind the antigen with a higher avidity, as a result of clonal selection in germinal centers. Previous studies showed how antibody avidity for pertussis toxin increases over time after infection or vaccination, then declining over time [ 19 ]. Analyzing the immune response to a measles-vectored chikungunya vaccine, Tschismarov et al [ 20 ] reported an increase in avidity with the second dose.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated antigenic stimulation leads to the selection of B cells that bear a receptor able to bind the antigen with a higher avidity, as a result of clonal selection in germinal centers. Previous studies showed how antibody avidity for pertussis toxin increases over time after infection or vaccination, then declining over time [ 19 ]. Analyzing the immune response to a measles-vectored chikungunya vaccine, Tschismarov et al [ 20 ] reported an increase in avidity with the second dose.…”
Section: Discussionmentioning
confidence: 99%
“…There are two other potential sources of variance between assays. Samples with a marginally weaker antibody avidity [28] may have a lower signal response, as the sample has a very limited time to react with the PT antigen on the test line during the flow of the sample in comparison to ELISA [24]. Second, the porous nitrocellulose material that the sample passes through in the LF test strip and the microtitre wells used in the ELISA are physically very different materials, which may lead to interference in antigen binding [29].…”
Section: Resultsmentioning
confidence: 99%
“…The CHO cell assay for pertussis toxin and Vero cell assay for diphtheria toxin is laborious, semi-quantitative, and less sensitive than ELISA-based readouts. Various studies have reported a positive correlation between the concentration of IgG antibodies and neutralization antibody titers ( 30 , 36 38 ). We also studied the agreement between the IgG concentrations estimated by bead-based assay and toxin-neutralization antibodies for pertussis and diphtheria toxin antigens.…”
Section: Discussionmentioning
confidence: 99%
“…The highest dilution of sera, which showed cluster neutralization, was recorded as the sample titer. A positive score was assigned when 10 or more CHO cell clusters were evident within a single well ( 30 ).…”
Section: Methodsmentioning
confidence: 99%